Evaluation of mechanical properties: Influence of glass fiber on banana fiber reinforced with epoxy composite. (2021) - Reddy, Maddigatla Vinod Kumar; Lakshmi, R.V.S.; Pragathi, Y.; Devaraj, P.; Naresh, N.
Abstract: Fiber reinforced polymer composites are superior strength, easy to fabricate and, their production cost is low compares with neat polymer resins, so these are majorly used in a many variety of applications. Reinforcement used in polymer is either natural (or) synthetic. Synthetic fiber such as carbon, glass etc, are higher cost of production so their application is in limited fields. Even though they have high specific strength. Recently due to their many advantages of natural fiber-based composites, their applications are more in various fields. In this connection for making value added products, an investigation has been carried out to make better utilization of banana fiber. The present Project work objective is evaluation of mechanical properties of Glass fiber influence on Banana fiber reinforced with epoxy composite. The effect of using glass fiber on mechanical properties of tensile, flexural, impact strength of banana/glass composites are studied. For these five different samples of composites were prepared like B(Banana), B(Banana)/G(Glass)/B(Banana), G(Glass)/B(Banana)/G(Glass), CB(Chopped Banana)/G(Glass)/CB(Chopped Banana), G(Glass)/CB(Chopped Banana)/G(Glass). From the results is clear that tensile, flexural and impact strength properties of banana fiber is greatly influenced by glass fiber.